Survival and growth in innovative technology entrepreneurship: A mixed-methods investigation - Stelios Eliakis; Dimosthenis Kotsopoulos; Angeliki Karagiannaki; Katerina Pramatari (Administrative Sciences, 2020)
Innovative technology enterprises are recognized internationally as an important pillar in modern economic activity. This paper presents the findings from a research combining qualitative and quantitative methods, with the specific goal of identifying and verifying the characteristics that affect their survival and growth. Results from an in-depth longitudinal qualitative case study, that examines a mature and constantly growing (in its 10-year operation) technologically innovative enterprise, reveal that a number of characteristics pertaining to both the profile of the entrepreneurial team, as well as of the employees, significantly affect company survival and growth in this context. Moreover, we recognize and analyze three stages in its evolution: an initial "evolutionary" growth (infancy and youth), followed by a "revolutionary" (crisis), and a second "evolutionary" (maturity) stage. Our findings are further corroborated and enriched through a survey with N = 27 entrepreneurs in innovative technology startups. We contribute to existing literature on innovative technology entrepreneurship, by identifying characteristics that entrepreneurs and employees should bear, towards its survival and growth. Moreover, a practical application of the life cycle approach is described for technologically innovative companies. Finally, a specific prescription that can help guide future theoretical and practical endeavors in innovative technology entrepreneurship is also provided accordingly.
Keywords: 350; case study; culture; employee; entrepreneurship; growth; innovative; liability of newness; longitudinal; organizational; survival; viability